2016
DOI: 10.1186/s40623-016-0554-6
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the mid-latitude trough position during different categories of magnetic storms and different storm intensities

Abstract: The ionospheric mid-latitude trough minimum position as a function of geomagnetic storm time is identified and investigated statistically in terms of the category and the intensity of storms. The data of ion density derived from DMSP and DEMETER satellites were used to extract the trough position. The variations of mid-latitude trough in 41 moderate magnetic storms and 88 intense magnetic storms in the 23rd solar cycle were studied. The results show that the trough moves toward the equator as Dst index decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Foster (1993) renamed the dusk effect “SED,” which is defined as the increase in the electron density with an increasing F region peak height and latitudinal stream‐like structure around the enhanced sunward convection region. Foster (1993) also showed that the SED phenomenon tends to appear equatorward in the midlatitude trough (e.g., Yang et al, 2015, 2016) and is caused by the equatorward expansion of the enhanced two‐cell convection associated with the development of geomagnetic storms.…”
Section: Introductionmentioning
confidence: 99%
“…Foster (1993) renamed the dusk effect “SED,” which is defined as the increase in the electron density with an increasing F region peak height and latitudinal stream‐like structure around the enhanced sunward convection region. Foster (1993) also showed that the SED phenomenon tends to appear equatorward in the midlatitude trough (e.g., Yang et al, 2015, 2016) and is caused by the equatorward expansion of the enhanced two‐cell convection associated with the development of geomagnetic storms.…”
Section: Introductionmentioning
confidence: 99%
“…The trough has been intensely investigated for several decades since Muldrew () first identified the trough with a topside sounder. Most previous studies found that the trough position mainly depends on the geomagnetic activity level, magnetic local time (MLT), and season (Ahmed et al, ; Annakuliev et al, ; Collis & Häggström, ; Ishida et al, ; Karpachev, Afonin, & Shmilauer, ; Karpachev, Deminov, & Afonin, ; Köhnlein & Raitt, ; Lee et al, ; Le et al, ; Oksman, ; Prolss, ; Pryse et al, ; Rycroft & Burnell, ; Spiro, Heelis, & Hanson, ; Tulunay, ; Tulunay & Grebowsky, ; Voiculescu, Virtanen, & Nygrén, ; Voiculescu & Nygrén, ; Yang et al, , ; Zou et al, ). The study on the longitudinal variation of the trough is restricted by the data availability, only a few studies focus on the longitudinal variation of the trough (Afonin et al, ; Besprozvannaya et al, ; He et al, ; Horvath & Lovell, , ; Karpachev & Afonin, ; Karpachev, ; Karpachev et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al [] found that the poleward wall can move equatorward rapidly after substorm onset with the speed of about 4° of geomagnetic latitude per hour. Yang et al [] found that the trough dynamics are different for different categories of magnetic storms. Compared to other storms, sheath storms cause the greatest variations in trough position.…”
Section: Introductionmentioning
confidence: 99%